2017
DOI: 10.18632/oncotarget.19935
|View full text |Cite
|
Sign up to set email alerts
|

Role of tissue-type plasminogen activator and plasminogen activator inhibitor-1 in psychological stress and depression

Abstract: Major depressive disorder is a common illness worldwide, but the pathogenesis of the disorder remains incompletely understood. The tissue-type plasminogen activator-plasminogen proteolytic cascade is highly expressed in the brain regions involved in mood regulation and neuroplasticity. Accumulating evidence from animal and human studies suggests that tissue-type plasminogen activator and its chief inhibitor, plasminogen activator inhibitor-1, are related to stress reaction and depression. Furthermore, the neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 97 publications
0
21
0
Order By: Relevance
“…The trkB signaling pathway involves many proteins that also possibly affect BDNF function. In addition, the proteolytic cleavage of proBDNF (a BDNF precursor with effects opposite to those of BDNF) to BDNF by plasmin determines the direction of BDNF action ( Lu et al, 2005 ; Tsai, 2017b ). Therefore, polymorphisms in the genes encoding proteins involved in the trkB or plasmin signaling pathway may interact with the BDNF Val66Met polymorphism to affect disease susceptibility ( Tsai, 2004a , 2007b ; Hwang et al, 2006 ).…”
Section: Bdnf Val66met Polymorphism and Gene–gene Interactiomentioning
confidence: 99%
“…The trkB signaling pathway involves many proteins that also possibly affect BDNF function. In addition, the proteolytic cleavage of proBDNF (a BDNF precursor with effects opposite to those of BDNF) to BDNF by plasmin determines the direction of BDNF action ( Lu et al, 2005 ; Tsai, 2017b ). Therefore, polymorphisms in the genes encoding proteins involved in the trkB or plasmin signaling pathway may interact with the BDNF Val66Met polymorphism to affect disease susceptibility ( Tsai, 2004a , 2007b ; Hwang et al, 2006 ).…”
Section: Bdnf Val66met Polymorphism and Gene–gene Interactiomentioning
confidence: 99%
“…It has been shown that exogenous tPA administration increases hippocampal BDNF levels and the conversion of pro‐BDNF to BDNF by plasmin is essential for LTP late‐phases . In addition, a defective tPA/plasmin/PAI‐1‐mediated BDNF maturation has been claimed to be involved in the manifestation of some brain pathologies, such as substance abuse and addiction, depression, and stress …”
Section: Plasminogen Activation System and The Regulation Of Bdnf Matmentioning
confidence: 99%
“…62,63 In addition, a defective tPA/plasmin/PAI-1-mediated BDNF maturation has been claimed to be involved in the manifestation of some brain pathologies, such as substance abuse and addiction, 64,65 depression, 66 and stress. 67 These data are not surprising given the fact that pro-BDNF and BDNF may have opposite effects on survival and function of CNS neurons.…”
Section: Pl a S Minog En Ac Tivati On Sys Tem And The Reg Ul Ati Onmentioning
confidence: 99%
“…PAI-1 is deposited in extracellular matrix, promotes the formation of lipoid and atheromatous plaque, thickens basement membranes, and hardens vessel walls, thus promoting the occurrence and development of vascular diseases ( 24 ). PAI-1 participates in the hydrolysis of brain-derived neurotrophic factor (BDNF) to regulate the growth and apoptosis of neurons, which are thought to be associated with depression ( 25 ). In addition, the tPA/PAI-1-plasmin system that involves PAI-1 can inhibit depressive behaviors induced by excitable neurotoxicity, which is caused by excessive activation of N-methyl-D-aspartic acid receptor (NMDA) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%